2002
DOI: 10.1021/jp026122q
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Alkali Metal Ion Recognition Processes at the Heptane/Water Interface by Second Harmonic Generation Spectroscopy

Abstract: Alkali metal ion recognition with [2-hydroxy-5-(4-nitrophenylazo)phenyl]-methyl-15-crown-5 (azoprobe 1) at the heptane/water interface was investigated by in situ second harmonic generation (SHG) spectroscopy. Upon addition of alkali metal ions, the second harmonic (SH) intensity of azoprobe 1 at the heptane/water interface was found to increase selectively. The observed selectivity of K+ > Na+ > Li+ > TMA+ was essentially the same order as that of the extractability for alkali metal ions in the 1,2-dichloroet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 32 publications
0
16
0
Order By: Relevance
“…This inherent technical difficulty has not been solved even today, and many SHG spectra reported so far have more or less similar data quality to the spectrum in Fig. 1b [2,10,12,13,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Electronic Sum Frequency Generation (Esfg)mentioning
confidence: 99%
“…This inherent technical difficulty has not been solved even today, and many SHG spectra reported so far have more or less similar data quality to the spectrum in Fig. 1b [2,10,12,13,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Electronic Sum Frequency Generation (Esfg)mentioning
confidence: 99%
“…The palladium(II)-2-(5-bromo-2-pyridylazo)-5-diethylaminophenol complex formed interfacial aggregates preferentially with purine bases (adenine and guanine). Alkali metal ion recognition with [2-hydroxy-5-(4-nitrophenylazo)phenyl]-methyl-15-crown-5 at the heptane-water interface was investigated by Teramae and co-workers, using in situ second harmonic generation (SHG) spectroscopy [ 85 ]. It was revealed experimentally that the Na + and K + complexes were flatter while the Li + complex exhibited a lift-up orientation at the heptane-water interface.…”
Section: Molecular Recognition At Other Interfacesmentioning
confidence: 99%
“…1,2 Totalinternal-reflection spectroscopy, [3][4][5][6] such as fluorescence spectroscopy (TIRF) [3][4][5] and Raman spectroscopy 6 , are the most frequently applied techniques on this subject; e.g., time-resolved TIRF was applied to observe the microenvironments of fluorescence molecules at the heptane/water interface where molecules around the interface had a low polarity or an extremely high viscosity of the microenvironment; 3 Ishizaka et al applied TIRF to calculate the thickness of the interface of carbon tetrachloride/water and 1,2-dichloroethane/water and so on, and suggested that the shape and thickness of the liquid/liquid interfaces were largely varied with the kind of solvents. 4,5 Second-harmonic generation (SHG) spectroscopy [7][8][9][10] is another technique that is highly sensitive and selective for molecules at a liquid/liquid interface; e.g., Nochi et al exhibited that SHG was applicable to alkali metal-ion recognition with the ionophore at the heptane/water, interface; also, the orientation change of the molecules at the interface was observed. 8 The polarities of water/1,2-dichloroethane and water/chlorobenzene interfaces were investigated by measuring the SH intensity of the polarity indicator molecules, which were found to be influenced by the polarity of the bulk phases.…”
Section: Introductionmentioning
confidence: 99%
“…4,5 Second-harmonic generation (SHG) spectroscopy [7][8][9][10] is another technique that is highly sensitive and selective for molecules at a liquid/liquid interface; e.g., Nochi et al exhibited that SHG was applicable to alkali metal-ion recognition with the ionophore at the heptane/water, interface; also, the orientation change of the molecules at the interface was observed. 8 The polarities of water/1,2-dichloroethane and water/chlorobenzene interfaces were investigated by measuring the SH intensity of the polarity indicator molecules, which were found to be influenced by the polarity of the bulk phases. 9 Recently, the time-resolved quasi-elastic laser scattering (QELS) method has been applied to study the behavior of a phase-transfer catalyst at the interface.…”
Section: Introductionmentioning
confidence: 99%